How to Recognize and Overcome Pulmonary Hypertension Crisis During Patent Ductus Arteriosus Closure by Device in Adult - Galuh, Lukitasari Ayu; Martini, Heny (Heart Science Journal, 2024)
BACKGROUND: Managing a patent ductus arteriosus (PDA) with severe pulmonary hypertension (PH) is challenging since closing the PDA can result in reduced cardiac output and right ventricular (RV) failure. The latest guideline for Adult Congenital Heart Disease (ACHD) stated it is harmful to close the defect in patients with pulmonary vascular resistance (PVR) â‰¤5 WU and flow ratio (FR) <1.5. Â CASE ILLUSTRATION: A 37-year-old female was referred with cough, fever, low saturation, and murmur findings. After serial examination, she was diagnosed with large PDA and severe PH her peripheral saturation (SaO2) was 88%-89% and non-responder to acute vasoreactivity test. After a year of PH therapy, vasoreactivity showed a response to the vasoreactivity test and improved on clinical presentation with SaO2 91%-92%. Patient fell in to PH crisis condition during the procedure of device closure, prostacyclin analogue intravenous (IV) and phosphodiesterase inhibitors inhalation was administered, and the procedure was carried on. The device was successfully implanted, and the patient had SaO2 97% in all four extremities before discharge.CONCLUSION: With established PH therapy, PDA with severe PH can underwent PDA closure by device with satisfying outcome.Â